Key Influencers of Intention to Use toward Internet of Things Devices for Residents in Hangzhou, China - Xiaoxiao, Shen (Scholar: Human Sciences, 2025)
Purpose: This study investigates factors affecting Hangzhou residents' intention to use IoT devices, using a conceptual framework to explore the relationships between information quality, data risk, financial risk, self-efficacy, motivation, perceived usefulness, perceived ease of use, and intention to use. Research Design and Methodology: Using a multi-stage sampling method, we conducted a quantitative survey with 472 valid responses from Hangzhou residents experienced with IoT devices. Confirmatory factor analysis (CFA) and structural equation modeling (SEM) were employed to analyze the data and test hypotheses. Results: Information quality and motivation enhance perceived usefulness. Motivation, data risk, and financial risk affect perceived ease of use, with data and financial risks negatively impacting it. Perceived ease of use is the strongest predictor of IoT use intention, followed by perceived usefulness and self-efficacy. Conclusions: The study validates and extends the technology acceptance model for IoT adoption, highlighting perceived ease of use, perceived usefulness, and self-efficacy as crucial factors. Improving information quality and addressing data and financial risks can enhance IoT adoption. Recommendations include optimizing user experience, establishing trust mechanisms, and developing accurate pricing strategies to stimulate adoption in the digital age. The findings are significant for advancing IoT technology acceptance.